City transport monitoring and routes optimal management system - Daunoras, Jonas; Bagdonas, Vaclovas; Gargasas, Vytautas (Transport, 2008)
The article analyses the problem of further development of geographic informational systems with traffic monitoring channel (GIS‐TMC) in order to present the road users with effective information about the fastest (the shortest in respect of time) routes and thus to improve the use of existing city transport infrastructure. To solve this task it is suggested to create dynamic (automatically updated in real time) street passing duration base, for support of which a city transport monitoring system operating in real time is necessary, consisting of a network of sensors, a data collection communications system and a data processing system. In the article it is shown that to predict the street passing duration it is enough to measure speed of transport in the characteristic points of the street. Measurements of traffic density do not significantly improve accuracy of forecasting the street passing time. Analytical formulas are presented meant to forecast the street passing time. First published online: 27 Oct 2010